Understanding the complexities of oral healthcare delivery in correctional settings: a qualitative exploration of barriers, facilitators, and opportunities - Amaya, Arianna; Medina, Ivan; Rezaei, Farimah; Soleimani, Pegah; Bosworth, Rebecca; Stöver, Heino; Moazen, Babak (BMC public health, 2025)
People living in prison face exceptionally high prevalence rates of tooth decay, periodontal disease, and poor oral health-related quality of life. Despite its importance, various aspects of oral healthcare in prison settings remain understudied. The present study investigates the barriers and facilitators associated with providing and utilizing oral health services in prison settings, drawing on insights from prison health experts, managerial and custodial staff, healthcare providers, and individuals with lived experience of imprisonment.
Gesehen am 29.01.2026